Effect on wettability of the topography and oxidation state of biaxially oriented poly(propylene) film. Issue 15 (3rd August 2019) - Strobel, Mark; Strobel, Joan M.; Jones, Viv; Lechuga, Hyacinth; Lyons, Christopher S.
Abstract: Surface topography and surface chemistry heterogeneity are widely accepted as causes of contact angle hysteresis. Contact angle hysteresis occurs on essentially all industrial polymer films. Four unmodified and flame-treated biaxially oriented poly(propylene) (BOPP) films produced from the same poly(propylene) base resin, but differing in surface topography and orientation, were characterized by measurement of the advancing and receding contact angles of water and diiodomethane, by atomic force microscopy (AFM) and by x-ray photoelectron spectroscopy (XPS). Contact angle hysteresis was much larger on flame-treated samples than on untreated samples even though some of the untreated films have significantly different topography at the nanoscale.